The role of flavonoids in autoimmune diseases: Therapeutic updates - Rengasamy, Kannan R R; Khan, Haroon; Gowrishankar, Shanmugaraj; Lagoa, Ricardo J L; Mahomoodally, Fawzi M; Khan, Ziyad; Suroowan, Shanoo; Tewari, Devesh; Zengin, Gokhan; Hassan, Sherif T S; Pandian, Shunmugiah Karutha (Pharmacology & therapeutics, 2019)
Flavonoids are natural polyphenolic compounds which are included in a panoply of drugs and used to treat and/or manage human ailments such as metabolic, cardiovascular, neurological disorders and cancer. Thus, the purpose of this review is to emphasize the importance of flavonoids for the treatment of autoimmune diseases and put into the limelight of the scientific community several health-promoting effects of flavonoids which could be beneficial for the development of novel drugs from natural products. Despite available reviews on flavonoids targeting various disease conditions, a comprehensive review of flavonoids for autoimmune diseases is still lacking. To the best of our knowledge, this is the first attempt to review the potential of flavonoids for autoimmune diseases. The structure-activity relationship of flavonoids in this review revealed that the rearrangement and introduction of other functional groups into the basic skeleton of flavonoids might lead to the development of new drugs which will be helpful in relieving the painful symptoms of various autoimmune diseases.
Keywords: autoimunitní nemoci; Inflammation; antiflogistika; Gene Expression Regulation; Autoimmune Diseases; Polyphenols; flavonoidy; regulace genové exprese; Animals; Flavonoids; zvířata; vztahy mezi strukturou a aktivitou; Anti-Inflammatory Agents; Humans; Immune system; Multiple sclerosis; Structure-Activity Relationship; Rheumatoid arthritis; lidé; Medicinal plants